UPAYA PENCEGAHAN FRAMBUSIA DENGAN EDUKASI ELIMINASI FRAMBUSIA PADA ANAK DAN KELUARGA - Murniati; Noor Yunida Triana; Indri Heri Susanti; Pramesti Dewi; Made Suandika (P3M Universitas Aisyiyah Surakarta, 2024)
Frambusia is an extremely contagious tropical disease. Indonesia is believed to have the highest number of frambusia instances in Southeast Asia, with 185 cases reported in 2021. The findings of serological examinations in numerous regions and cities suggest that the prevalence of frambusia is 20-120 per 100,000 people aged 1 to 15. Efforts to fight frambusia can be carried out through health promotion. A pre-survey at SD N 01 Dukuh Waluh, conducted through interviews with ten students, revealed that students had never received health education about frambusia and had no idea what the disease was. This program aims to educate students and their parents about frambusia and its prevention. The activity took place on Wednesday, March 15, 2023, at SD N 01 Dukuhwaluh, with 16 parents and 35 5th grade kids in attendance. The results of the program after health education revealed that the majority of respondents' knowledge increased (75%), knowledge remained constant by up to 25%, and no respondents (0%) had knowledge decreased. This exercise is expected to offer children and parents with a thorough awareness of Frambusia, as well as to encourage the adoption of clean and healthy living habits in order to prevent the disease. Keywords: Health education; Prevention; Frambusia; Children; Elementary School.